2021
DOI: 10.3390/ijms22041647
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Developed Synbiotic Yogurt Prevents Diabetes by Improving the Microbiome–Intestine–Pancreas Axis

Abstract: The prevalence of type 2 diabetes mellitus (T2D) is increasing worldwide, and there are no long-term preventive strategies to stop this growth. Emerging research shows that perturbations in the gut microbiome significantly contribute to the development of T2D, while microbiome modulators may be beneficial for T2D prevention. However, microbiome modulators that are effective, safe, affordable, and able to be administered daily are not yet available. Based on our previous pro- and prebiotic studies, we developed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…plantarum D6-2, and L. rhamnosus D4-4 possessed potentials to reduce lipid content and blood glucose levels, subsequently alleviating diet-induced hyperlipidemia and hyperglycemia. In the present study, LA-Y supplementation obviously reduced body weight, fat index, liver index, triglyceride content, and fasting blood glucose level and improved glucose tolerance and insulin sensitivity (Figures and ), indicating that LA-Y could suppress lipid and glucose accumulation.…”
Section: Discussionsupporting
confidence: 51%
“…plantarum D6-2, and L. rhamnosus D4-4 possessed potentials to reduce lipid content and blood glucose levels, subsequently alleviating diet-induced hyperlipidemia and hyperglycemia. In the present study, LA-Y supplementation obviously reduced body weight, fat index, liver index, triglyceride content, and fasting blood glucose level and improved glucose tolerance and insulin sensitivity (Figures and ), indicating that LA-Y could suppress lipid and glucose accumulation.…”
Section: Discussionsupporting
confidence: 51%
“…Beneficial microorganisms should be kept viable in fermented milk products such as yogurt before consumption. According to many scientific studies, inulin, as a fermentation substrate, has been reported to be beneficial for the growth of probiotics in the production of fermented milk products [40]. In general, the total number of LAB in yogurt was more than at least 10 7 living microorganisms per gram.…”
Section: Discussionmentioning
confidence: 99%
“…They were also found to stimulate the growth of Bifidobacterium (B. longum, B. breve, B. bifidum, B. pseudocatenulatum) and enhance the efficiency of environmental colonization by these bacteria [207,210]. The administration of a synbiotic in the form of yogurt significantly reduced the development of hyperglycemia in streptozotocin-induced diabetic mice compared to the group receiving milk [211]. Synbiotic yoghurt favorably modulated the composition of the intestinal microbiota and protected the morphology of the pancreatic islets, thus preventing hyperglycemia through the microbiome-gut-pancreas axis.…”
Section: Communication Between Microorganisms and Epithelial Cells Re...mentioning
confidence: 99%